1998
DOI: 10.1523/jneurosci.18-21-08648.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Localization of the Brain-Specific Inorganic Phosphate Transporter Suggests a Specific Presynaptic Role in Glutamatergic Transmission

Abstract: Molecular cloning has recently identified a vertebrate brain-specific Na+-dependent inorganic phosphate transporter (BNPI). BNPI has strong sequence similarity to EAT-4, a Caenorhabditis elegans protein implicated in glutamatergic transmission. To characterize the physiological role of BNPI, we have generated an antibody to the protein. Immunocytochemistry of rat brain sections shows a light microscopic pattern that is suggestive of reactivity in nerve terminals. Excitatory projections are labeled prominently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
271
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(315 citation statements)
references
References 55 publications
41
271
1
2
Order By: Relevance
“…The observed pattern of VGLUT1 immunoreactivity in the dorsal hippocampus of control mice was consistent with previous reports (Bellocchio et al, 1998;Fremeau et al, 2001;Varoqui et al, 2002) demonstrating widespread expression, with the exception of granule and pyramidal cell layers, and particular enrichment in stratum oriens and radiatum of CA1 as well as the molecular and polymorphic layers of the dentate gyrus (Figure 4a, left). All VGLUT1 staining was abolished by preadsorption of the primary antibody with a VGLUT1 control peptide (data not shown).…”
Section: Intrahippocampal Administration Of Vglut1-targeting Shrna Sesupporting
confidence: 92%
See 1 more Smart Citation
“…The observed pattern of VGLUT1 immunoreactivity in the dorsal hippocampus of control mice was consistent with previous reports (Bellocchio et al, 1998;Fremeau et al, 2001;Varoqui et al, 2002) demonstrating widespread expression, with the exception of granule and pyramidal cell layers, and particular enrichment in stratum oriens and radiatum of CA1 as well as the molecular and polymorphic layers of the dentate gyrus (Figure 4a, left). All VGLUT1 staining was abolished by preadsorption of the primary antibody with a VGLUT1 control peptide (data not shown).…”
Section: Intrahippocampal Administration Of Vglut1-targeting Shrna Sesupporting
confidence: 92%
“…VGLUT1 is expressed in a distinct laminar pattern throughout the dorsal hippocampus, with particular enrichment in the polymorphic and molecular cell layers. Localization to strata oriens and radiatum of CA1 suggests expression in terminals of the Schaffer collateral system, presence in stratum lucidum of CA3 represents expression in mossy fiber terminals from dentate granule cells, and stronger labeling in outer regions of the molecular layer of the dentate gyrus indicates preferential localization to perforant path inputs from the entorhinal cortex (Bellocchio et al, 1998;Fremeau et al, 2001;Varoqui et al, 2002). Despite low VGLUT2 expression in the pyramidal layer of CA2 and the granular layer of the dentate gyrus (Fremeau et al, 2001), there is no evidence for coexpression of both transporters within individual nerve terminals (Herzog et al, 2001), and a recent detailed study found no evidence for VGLUT1 expression in hippocampal astrocytes (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic structures were identified as the dendritic spines of granule neurons, traced from the GCL, but the origin of presynaptic axons is less clear. The majority of glutamatergic inputs to the dentate gyrus originate from the entorhinal cortex (43), but cortical inputs mainly terminate in the outer two thirds of the ML (64)(65)(66)(67)(68). The dense arborizations of NGPα RGL stem cells are predominantly contained within the inner third of the ML and GCL, a region where subcortical inputs predominantly terminate (69).…”
Section: Discussionmentioning
confidence: 99%
“…VGLUT1 mRNA and protein is expressed in most pyramidal neurons in situ (Ni et al, 1995;Bellocchio et al, 1998), and VGLUT1-encoded excitatory synapses predominate in adult neocortex (Fremeau et al, 2004a) as they do in differentiated neocortical cultures (DIV21). VGLUT2-expressing puncta are evenly distributed in differentiated cultures, like VGLUT1, but are reduced in number (ϳ25%).…”
Section: Coordinated Endogenous Upregulation Of Vglut1 and Viaat Durimentioning
confidence: 99%